Childhood adversity and cardiovascular disease risk: An appraisal of recall methods with a focus on stress-buffering processes in childhood and adulthood. (February 2020) - Lei, Man-Kit; Berg, Mark T.; Simons, Ronald L.; Simons, Leslie G.; Beach, Steven R.H.
Abstract: Introduction: Associations between childhood/adolescent adversity and poor adult physical health have been reported in past work. Much of this work has relied on either retrospective or prospective measures of childhood experiences. However, the effect of different assessment methods on potential stress buffering processes remains largely unknown. Objective: We first examined the extent to which long-term cardiovascular disease risk (CVD) was predicted by reports obtained from 10-year old youth regarding adversity experienced in the prior year and those obtained from the same individuals as adults (age 29) regarding their experience of childhood adversity from ages 0–10, focusing in each case on similar types of adversity. To test stress buffering perspectives, we examined the effects of parental emotional support on the association between each measure of childhood adversities and cardiovascular health. Methods: We used data from a longitudinal sample of 454 African Americans enrolled in the Family and Community Health Study. The outcome variable was a 30-year CVD risk score computed from the Framingham algorithm. The hypotheses were tested with beta regression models. Results: The findings revealed a link between childhood adversity and adult CVD risk at age 29, for both measures of adversity. Consistent with the stress-buffering hypothesis, prospectively assessed parental emotional support in adolescence, but not adulthood, buffered effects on cardiovascular risk for each type of assessment of childhood adversity. Conclusions: Prospective and retrospective measures correlated in a manner similar to prior reports (i.e. significantly, but poorly). Further, in line with stress-buffering hypothesis, parental emotional support received at age 10 yielded different buffering effects than parental emotional support received at age 29. The study's findings suggest that theoretically consistent patterns of stress-buffering are detectable using either type of assessment of childhood adversity and provide useful information in the prediction of adult CVD risk. Highlights: Cardiovascular risk was predicted by prospective measures of childhood adversity. Retrospective measures also reliably predicted cardiovascular risk. Both relationships were buffered by parental emotional support at age 10. Identifying buffering processes will guide intervention efforts.